PELATIHAN MEMBUAT ANGGARAN KAS PADA USAHA KECIL WARUNG NASI UDUK PAK TEGUH, JAKARA UTARA - Rorlen Rorlen; Vincent Aldo Zaini; Sherliana Lim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Mr Teguh’s establishment was found in 2006 outside of an elementary school in a residential area of Sunter Hijau, North Jakarta. Mr and Mrs Teguh are from Semarang, who try to make a living in Jakarta using her cooking skill. Within the first few years, their establishment which sells vegetable rice was quite promising. This is due to the high number of housewives who shop when dropping and picking up their children at school. As time goes by, more establishments similar to theirs emerge within the school and residential area. This affects Mr Teguh’s income considerably so that he switched to selling nasi lemak and other snacks exclusively in the morning. Mr and Mrs Teguh’s main concern is that they never know their exact profit in a month or certain period of time. This is due to their habit of only counting their daily revenue. And so it goes with their expense; only based on daily estimation. Sometimes when the sales are not too good, they have to bring the leftover home without being able to count their loss. These are the reasons why my team and I intend to help Mr and Mrs Teguh with community engagement so that it will hopefully guide them to structure their income and expenditure as well as forecasting them. It will also hopefully decrease their uncalculated costs and losses. The method that will be exercised is Training Material Extension Method so it can help Mr Teguh in their budgeting. The exercise will be done online. This community engagement starts by giving them modules of counselling and explanation as well as budgeting trial. Outside target that we hopefully achieve is publication articles.